2021
DOI: 10.1111/chso.12482
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance, obedience and resistance: Children's perceptions of street trading in Nigeria

Abstract: Recent attempts in Nigeria to implement children's rights and extend education beyond primary level appear to be challenging. Drawing on interviews and focus groups with 17 child traders aged 10-15 in a market town in Nigeria, this article reflects on tensions emerging from children's participation in trading during school hours, despite the implementation of the United Nations' Convention on the Rights of the Child (CRC; United Nations, 1989), the African Charter on the Rights and Welfare of the Child (ACC; O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Considering the high-power distance in Nigeria, children may feel obliged to listen to authority. Osaiyuwu et al (2022) found that Nigerian children who were told to engage in street trading by parents or older family members believed they had a duty to obey their parents/elders irrespective of the situation. However, the reasoning behind these low endorsements in the current study is unclear because we did not examine reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high-power distance in Nigeria, children may feel obliged to listen to authority. Osaiyuwu et al (2022) found that Nigerian children who were told to engage in street trading by parents or older family members believed they had a duty to obey their parents/elders irrespective of the situation. However, the reasoning behind these low endorsements in the current study is unclear because we did not examine reasoning.…”
Section: Discussionmentioning
confidence: 99%